Designing a Rural Development Strategy for Peru's Sierra - Werbrouck, Pierre (World Bank, Washington, DC, 2012)
Poverty and economic stagnation characterize most rural areas in Peru. National growth has been slow and uneven since the mid-1970s, benefiting urban areas rather than rural ones. Between 1985 and 2000, the number of poor people increased by 71 percent. The incidence of poverty (67 percent) and extreme poverty (40 percent) is highest in rural areas, reaching 73 percent (poverty) and 41 percent (extreme poverty) in the sierra. This means that 4.2 million rural people live with incomes 30 percent below the poverty line and 2.3 million people live in extreme poverty. Regional specific policies to fight poverty may be warranted, notably a strategy for rural development in the sierra aiming for more equitable economic growth and reduced poverty. This brief includes the following headlines: detailed analysis; recommendations; notes; lessons learned; about the author; and about 'en breve'.